Cognitive Functioning in Older People. Results of the First Wave of Cognition of Older People, Education, Recreational Activities, Nutrition, Comorbidities, Functional Capacity Studies (COPERNICUS) - Kujawski, Sławomir; Kujawska, Agnieszka; Gajos, Małgorzata; Topka, Weronika; Perkowski, Radosław; Androsiuk-Perkowska, Joanna; Newton, Julia L.; Zalewski, Paweł; Kędziora-Kornatowska, Kornelia (Frontiers in Aging Neuroscience, 2018)
Background: Cognitive reserve as a way of explanation of why some individual with high degree of brain pathology are without clinical manifestations. Factors related to systemic diseases, body composition, aerobic capacity, past and current behavior were examined and included as predictors of cognitive function. Materials and methods: 407 subjects (60-88 years old) underwent physical examination and cognitive function assessment (Mini–Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA) and Trail Making Test Part B (TMT B)). Predictors of cognitive functioning were evaluated: occupational status (OS), diet, mental and touristic activities were assessed using ad hoc questionnaire. Aerobic capacity was measured using six-minute walk test (6MWT). Results: With each year of age there is a decrease in MMSE score by 0.18 point. Varicose veins on lower extremities and low OS were also significantly associated with MMSE result. For every year of having hypertension, low OS and not being abroad in the last three years, there was 0.17, 0.30 and 0.16 less points, respectively, and 0.15 more point per one additional meter walked in 6MWT in the MoCA score. With each year of age and for low OS there was there was 0.31 and 0.21 second more to complete TMT B, respectively. Conclusion: Education, OS, presence of systemic diseases and social and tourist activities, aerobic capacity and body composition could be consider as factors contributing to cognitive functioning in older people. However, the relationship of above mentioned factors with education level and cognitive function may be not fully orthogonal.